From Waste to Taste: Developing Upcycled Coffee Ground Cookies for Sustainable Consumption - Peralta, Kristine A.; Nebrida, Joan M.; Agcaoili, Czaira Ashley S.; De Jesus, Jomari A.; Enrique, C-Jay G.; Nebrida, Alan (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study evaluated the acceptability of upcycled coffee ground cookies by analyzing their sensory attributes—appearance, aroma, texture, taste, and overall acceptability—across four different treat-ments. The experiment aimed to determine consumer preferences for these cookies, with each treatment containing a different percentage of coffee grounds, ranging from 100% in treatment 1 to 25% in treatment 4. The accepted treatment 2 (75%) was subjected to nutri-tional analysis. While the characteristics of the cookies differed, each had a consistent diameter of 8 cm. The sensory evaluation revealed that the treatment with 75% coffee grounds received the highest rat-ings across all categories, indicating that consumers found it particu-larly acceptable in terms of appearance, aroma, texture, and taste. Meanwhile, traditional butter cookies also received high ratings, re-flecting strong consumer preference. However, no significant correla-tion was observed between the sensory ratings of the butter cookies and the upcycled coffee ground cookies, suggesting that consumers perceived these as distinct products. Preference for one did not influ-ence perceptions of the other. The study concludes that offering a va-riety of products with different concentrations of upcycled coffee grounds and flavor profiles can effectively cater to the diverse tastes of consumers. Additionally, the recommended serving size is two cookies, totaling 24 grams.